Genetically Determined Circulating Levels of Cytokines and the Risk of Rheumatoid Arthritis - Qian, Yu; He, Zhixing; Zhao, Sizheng Steven; Liu, Bin; Chen, Ying; Sun, Xiaohui; Ye, Ding; Jiang, Xia; Zheng, Hui; Wen, Chengping; Zheng, Houfeng; Mao, Yingying (Frontiers in Genetics, 2022)
Background: Accumulation of inflammatory leukocytes in articular tissues is the hallmark feature of rheumatoid arthritis (RA). Increasing evidence from observational studies has suggested that several cytokines may be involved in the development of RA. However, traditional observational studies are susceptible to bias from confounding and reverse causation; therefore, the potential causal relationships of individual cytokines with the risk of RA remain elusive. Objective: In this study, we evaluated whether genetically determined circulating levels of cytokines were associated with the risk of RA by performing Mendelian randomization (MR). Methods: We identified single nucleotide polymorphisms (SNPs) associated with circulating levels of cytokines and growth factors from a genome-wide association study (GWAS) including 8,293 participants of Finnish ancestry as instrumental variables (IVs). The association estimates of these IVs with the risk of RA were obtained from a GWAS meta-analysis including 14,361 RA cases and 43,923 controls of European ancestry. We conducted a series of MR analyses to assess the relationship between genetically determined circulating cytokines and the risk of RA, including the random-effects inverse variance-weighted, weighted-median, MR-Egger regression, and MR pleiotropy residual sum and outlier tests. For potential cytokine-RA associations supported by MR evidence, sensitivity analyses were further performed using restricted IV sets of SNPs with colocalization evidence and that excluding pleiotropic SNPs. Results: In the primary MR analysis, there was a suggestive inverse association between genetically determined circulating level of macrophage inflammatory protein-1β (MIP-1b) and the risk of RA [odds ratio (OR): 0.95, 95% confidence interval (CI) = 0.92-0.99, P = 0.016]. The effect estimates were similar in alternative MR analyses. Among SNPs used as IVs for MIP-1b, we found 92 SNPs without documented pleiotropy and three SNPs with evidence of colocalization. The association of MIP-1b with RA from sensitivity analyses using these two sets of restricted IVs remained stable. Conclusions: Our study suggests that genetically determined elevated circulating level of MIP-1b may be associated with a lower risk of RA. Further studies are warranted to determine how MIP-1b and related pathways may contribute to the development of RA.